PENGARUH HARGA, KUALITAS PELAYANAN, KEPERCAYAAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIANPONSEL - Nur Fachodhi, 09.05.51.0037 (Students Journal of Economic and Management, 2013)
Research Entitled Effect Of Price, Quality Service, Trust And Campaign Against Mobile Purchase Decision (Studies In Semarang Trade Center (Sctc) Matahari Plaza Semarang Simpang Lima Thisisa Study To Determineand Analyze Whet HerÂ  The Variable Price, Quality Of Service, Trust, And The Promotion Of Semarang Celular Trade Center (Sctc) Matahari Plaza Semarang Simpang Lima Significantly Influence Customers Purchasing Decisions Semarang Celular Trade Center (Sctc). Authors There For Take The Title"The Effect Of Price, Quality Service, Trust And Promotion Decisions ToÂ  Purchase Phone(Studies In Semarang Celular Trade Center (Sctc) Matahari Plasa Simpang Lima Semarang) ".The Samples Us Â This Study Were 80 Respondents. The Technique Use Dinthis Study UsedÂ  Purposive Sampling To Select Respondents Or According To There Quirements To Become A RespondenÂ  Made ââA Purchasein Semarang Celular Trade Center (Sctc) At Least 3 Times. The Collected Data Istested First By Using Test Validity And Reliability In Order To Obtain Valid And Reliable Results That Can Be Use Dinsubsequent testing. Obtained From The Test Results That The Variable Quality Of Serviceis More Powerful Than The Price Variables, Customer Comfort When Making A Purchasein Semarang Celular Trade Center (Sctc) Is Rated By Customers Semarang celular trade center (Sctc). This Study has keterbatasanya the variables Used only In The dimension Of price, Quality Of Service, Trust And Promotion, While There Are Many Other Factors That Can Influencea Customers Buying Decision. There Fore, Further Researchis Suggested To Consider Other Variables That Have Not Been Found In This Study And A Wider Sampling. Keywords : Price, service qualty, trust, promotion and purchase decisions